Penerapan Model Pembelajaran Kooperatif Tipe STAD dalam Pembelajaran Fiqh di Madrasah Ibtidaiyah - Setiawan, Ajang Santa; Awaludin, Mukti; Ferianto, Ferianto (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to describe the implementation of STAD cooperative learning model in learning fiqh grade IV in madrasah Ibtidaiyah. The research used a qualitative approach with a case study method involving data collection through interviews, document study and observation. Data analysis used triangulation and research team group discussion. The research was conducted at Madrasah Ibtidaiyah Tarbiyatul Islam 01 Karawang involving teachers and grade IV students. The results of the study showed that the application of the STAD type cooperative learning model provided a number of positive impacts and results, such as increasing social interaction between students, strengthening collaborative skills, and building confidence in communicating and sharing ideas. This model also increases learning motivation, increases class participation, and encourages the development of problem-solving and critical thinking skills through group discussion and collaboration. Despite facing obstacles such as intensive preparation and effective group management, the application of the STAD model in Fiqh learning has a significant positive impact on the quality of learning and student learning outcomes.